Influence of dipolar interactions on the angular-dependent coercivity of nickel nanocylinders. (15th April 2015) - Bender, P; Krämer, F; Tschöpe, A; Birringer, R
Abstract In this study the influence of dipolar interactions on the orientation-dependent magnetization behavior of an ensemble of single-domain nickel nanorods was investigated. The rods were synthesized by electrodeposition of nickel into porous alumina templates. Some of the rods were released from the oxide and embedded in gelatine hydrogels (ferrogel) at a sufficiently large average interparticle distance to suppress dipolar interactions. By comparing the orientation-dependent hystereses of the two ensembles in the template and the gel-matrix it could be shown that the dipolar interactions in the template considerably alter the functional form of the angular-dependent coercivity. Analysis of the magnetization curves for an angle of 60° between the rod-axes and the field revealed a significantly reduced coercivity of the template compared to the ferrogel, which could be directly attributed to a stray field induced magnetization reversal of a steadily increasing number of rods with increasing field strength. The magnetization curve of the template could be approximated by a weighted linear superposition of the hysteresis branches of the ferrogel. The magnetization reversal process of the rods was investigated by analyzing the angular-dependent coercivity of the non-interacting nanorods. Comparison of the functional form with analytical models and micromagnetic simulations emphasized the assumption of a localized magnetization reversal. Additionally, it could be shown that the nucleation field of rods with diameters in the range 18–29 nm tends to increase with increasing diameter.